Mean excitation energy determination for Monte Carlo simulations of boron carbide as degrader material for proton therapy. (December 2020) - Psoroulas, S.; Meer, D.; Oponowicz, E.; Owen, H.
Highlights: We estimated the mean excitation energy of B4C comparing data to Geant4 simulations. Our estimate (83.1  ±  2.8 eV) agrees with the ICRU estimate but is more precise. The experiment uses standard dosimetric equipment for proton therapy facilities. The method does not require precise knowledge of the incident beam energy. The method should be used with accurate physics models in Monte Carlo simulations. Abstract: Boron carbide is a material proposed as an alternative to graphite for use as an energy degrader in proton therapy facilities, and is favoured due to its mechanical robustness and promise to give lower lateral scattering for a given energy loss. However, the mean excitation energy of boron carbide has not yet been directly measured. Here we present a simple method to determine the mean excitation energy by comparison with the relative stopping power in a water phantom, and from a comparison between experimental data and simulations we derive a value for it of 83.1  ±  2.8 eV suitable for use in Monte-Carlo simulation. This is consistent with the existing ICRU estimate (84.7 eV with 10–15% uncertainty) that is based on indirect Bragg additivity calculation, but it has a substantially smaller uncertainty. The method described can be readily applied to predict the ionisation loss of other boron carbide materials in which the atomic constituent ratio may vary, and allows this material to be reliably used as an alternative to graphite, diamond or beryllium.